Avian diversity and behavior in an Eocene coastal plain, Svalbard: the ichnological evidence - Melchor, Ricardo Nestor; Uchman, Alfred; Steel, Ronald J. (Ichnos)
This study presents an ichnotaxonomical assessment of bird footprints from a coastal plain setting in the Eocene lower to middle Aspelintoppen Formation in Brongniartfjellet and Storvola, Svalbard. These footprints are unique evidence for Paleogene birds from Svalbard and the second evidence of Paleogene avifauna of the Arctic (along with scarce fossil remains from Ellesmere Island). The analyzed footprints are assigned to six ichnotaxa belonging to three ichnofamilies: Aquatilavipes isp., avian footprint morphotype A and B (ichnofamily Avipedidae); Gruipeda cf. G. abeli, Gruipeda cf. G. dominguensis (ichnofamily Gruipedidae); and Gyeongsangornipes isp. (ichnofamily unknown). Associated invertebrate ichnofossils include Helminthoidichnites tenuis, Cochlichnus anguineus, and Helminthopsis isp. The avian footprints reflect small, medium-sized and rare large birds that can be morphologically compared to those of modern relatives including crane, heron, plover, moorhen, gallinule, oystercatcher and curlew. It is also proposed that in situ sets of shorebird footprints showing a preferred orientation, not composing trackways and showing overprinting, can be used as an indicator of the position and orientation of the shoreline. Fil: Melchor, Ricardo Nestor. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Ciencias de la Tierra y Ambientales de La Pampa. Universidad Nacional de La Pampa. Facultad de Ciencias Exactas y Naturales. Instituto de Ciencias de la Tierra y Ambientales de La Pampa; Argentina Fil: Uchman, Alfred. Jagiellonian University; Polonia Fil: Steel, Ronald J. University of Texas at Austin; Estados Unidos